Collaborative participation in aphasic word searching: comparison between significant others and speech and language therapists - Minna Laakso (Routledge Taylor & Francis Group, 2022)
Background: Searching for words is a common phenomenon in conversations of the people with aphasia. When searching for a word the speaker interrupts the emerging conversational turn with a pause, vocalisation (e.g., uh) and/or a question (e.g., what is it). Previous studies suggest that gazing and pointing can be used to invite conversational partners to join the search.
Aims: This study compares the collaborative actions of different conversational partners (significant others vs. speech and language therapists of people with aphasia) during aphasic word searching. The aphasic speakers’ actions inviting assistance from the partners in the search are also examined.
Methods & Procedures: The data for the study comprised 20 conversations, half videotaped at the participants’ homes and half in aphasia therapy sessions. The conversations were transcribed and analysed sequentially with a special emphasis on taking non-verbal actions into account. In the analysis, word search sequences were identified and the collaborative participation of the significant others, as well as the speech and language therapists, compared.
Outcomes & Results: The analysis showed that institutional and non-institutional conversational partners collaborate in different ways during word searching. When invited to join the search, often nonverbally, the significant others quickly offer words for the aphasic speakers to complete the search. When successful, these immediate completions solve the search and the core conversation can continue. On the other hand, even if invited nonverbally, speech and language therapists do not join in searching by offering words. Instead, they ask questions or offer their candidate understandings that are more elaborate than one word. Furthermore, they regularly shift the speaking turn back to the aphasic speaker encouraging the aphasic speaker to continue the search by him or herself.